MRI Findings in Cryptococcal Meningitis of the Non-HIV Population. Issue 2 (January 2015) - Sarkis, Rani A.; Mays, Maryann; Isada, Carlos; Ahmed, Manzoor
<x xml:space="preserve">Abstract</x> Objectives: Cryptococcal meningitis is an opportunistic infection which can afflict immunocompetent and immunocompromised individuals. Imaging findings in the HIV population are well described; however, few studies have focused on the non-HIV population. The purpose of this study is to characterize clinical and magnetic resonance imaging (MRI) findings in the non-HIV population. Methods: We performed a retrospective chart review of patients with positive CSF cryptococcal antigen (between 1997 and 2009) who were not HIV positive. Only patients with MRIs of the brain were included. Data collected included CSF findings, blood and CSF cryptococcal titers, and information regarding the use of immunosuppressant drugs. Results: Nineteen patients fulfilled study criteria, and 74% of the patients had abnormal imaging. Ten patients were on immunosuppressants due to cancer, organ transplantation, or presumed vasculitis. Four patients had no known risk factors and 2 patients had idiopathic low CD4 counts. MRI findings in cryptococcal meningitis included leptomeningeal enhancement with or without a micronodular pattern, microcystic prominence involving the temporal lobes or basal ganglia, ventriculomegaly, and a brain abscess. Two patients had posterior fossa cysts at the foramen of Luschka. Five patients had a normal MRI. Conclusions: MRI findings in cryptococcal meningitis of the non-HIV population were more common in our series than previously recognized. In this patient population, leptomeningeal enhancement and intraventricular cystic lesions were more common than intraparenchymal findings.